A Scaffolding Empathic Methodology in the Robotics Teacher Formation Using Log Book and the BNCC References - Minami, Mario; Gomes, Marco; Suyama, Ricardo; Panazio, Aline; Takahata, Andre; Kurashima, Celso; Moura, Fernando; Kleinschmidt, João; Junior, Lunequel (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The adoption of active teaching methodologies in schools aims to provide students with a greater role in all classroom activities, and seeks the development of important skills for the 21st century. In this scenario, Robotics Teacher Formation is a challenge to this interdisciplinary and very attractive theme. This paper presents an improvement of Formative Assessment methodology applied to Robotics Teacher Education in public schools with scaffolding strategies. Our proposal focus on a greater care in the use of cooperative Log-Book records and empathic approach, as well as in the digital planning of interdisciplinary activities using the skills proposed in the Curricular Common National Base BNCC).